RADIOIMMUNOASSAY FOR DETECTION OF ANTI-RINDERPEST ANTIBODIES IN CATTLES - ALI, HM.; MOHAMMAD, G.S.; ABDULKARIM, HM. (The Iraqi Journal of Veterinary Medicine, 2022)
Liquid Phase Radioimmunoassay (RIA) was developed to detect and measure anti-rinderpest immunoglobulins in field animals sera, within two hours. Rinderpest virus adapted on Vero cell line culture and antigen purified by treatment with Triton-Gentron 13 Butanol, and, labeled with I isotope, using chloramin T iodination method. Comparative studies for detecting anti-rinderpest immunoglobulin in 80 calves sera samples, using the developed assay in parallel with virus neutralization test (VNT). The study showed 58.75 % agreement between the two methods. However, 71 % of seven months old, non-vaccinated calves showed anti rinderpest antibodies in their sera, also 81 % of 10 months old vaccinated calves were developed antibodies in their blood. These results demonstrate the development of sensitive, specific and rapid quantitative / qualitative radioimmunoassay, necessary for screening the development of immunity against rinderpest in cattle.